Associations of Bariatric Surgery With Changes in Interpersonal Relationship Status: Results From 2 Swedish Cohort Studies - Bruze, Gustaf; Holmin, Tobias E; Peltonen, Markku; Ottosson, Johan; Sjöholm, Kajsa; Näslund, Ingmar; Neovius, Martin; Carlsson, Lena M. S; Svensson, Per-Arne (JAMA surgery, 2018)
IMPORTANCE: Bariatric surgery is a life-changing treatment for patients with severe obesity, but little is known about its association with interpersonal relationships. OBJECTIVES: To investigate if relationship status is altered after bariatric surgery. DESIGN, SETTING, AND PARTICIPANTS: Changes in relationship status after bariatric surgery were examined in 2 cohorts: (1) the prospective Swedish Obese Subjects (SOS) study, which recruited patients undergoing bariatric surgery from September 1, 1987, to January 31, 2001, and compared their care with usual nonsurgical care in matched obese control participants; and (2) participants from the Scandinavian Obesity Surgery Registry (SOReg), a prospective, electronically captured register that recruited patients from January 2007 through December 2012 and selected comparator participants from the general population matched on age, sex, and place of residence. Data was collected in surgical departments and primary health care centers in Sweden. The current analysis includes data collected up until July 2015 (SOS) and December 2012 (SOReg). Data analysis was completed from June 2016 to December 2017. MAIN OUTCOMES AND MEASURES: In the SOS study, information on relationship status was obtained from questionnaires. In the SOReg and general population cohort, information on marriage and divorce was obtained from the Swedish Total Population Registry. RESULTS: The SOS study included 1958 patients who had bariatric surgery (of whom 1389 [70.9%] were female) and 1912 matched obese controls (of whom 1354 [70.8%] were female) and had a median (range) follow-up of 10 (0.5-20) years. The SOReg cohort included 29 234 patients who had gastric bypass surgery (of whom 22 131 [75.6%] were female) and 283 748 comparators from the general population (of whom 214 342 [75.5%] were female), and had a median (range) follow-up of 2.9 (0.003-7.0) years. In the SOS study, the surgical patients received gastric banding (n = 368; 18.8%), vertical banded gastroplasty (n = 1331; 68.0%), or gastric bypass (n = 259; 13.2%); controls received usual obesity care. In SOReg, all 29 234 surgical participants received gastric bypass surgery. In the SOS study, bariatric surgery was associated with increased incidence of divorce/separation compared with controls for those in a relationship (adjusted hazard ratio [aHR] = 1.28; 95% CI, 1.03-1.60; P = .03) and increased incidence of marriage or new relationship (aHR = 2.03; 95% CI, 1.52-2.71; P < .001) in those who were unmarried or single at baseline. In the SOReg and general population cohort, gastric bypass was associated with increased incidence of divorce compared with married control participants (aHR = 1.41; 95% CI, 1.33-1.49; P < .001) and increased incidence of marriage in those who were unmarried at baseline (aHR = 1.35; 95% CI, 1.28-1.42; P < .001). Within the surgery groups, changes in relationship status were more common in those with larger weight loss. CONCLUSIONS AND RELEVANCE: In addition to its association with obesity comorbidities, bariatric surgery–induced weight loss is also associated with changes in relationship status.